Relation beetween Profitability, Leverage, and Firmsize on Tax Avoidance - Muhammad Andri Radiany; Wulandari Harjanti; Ali Farhan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is intended to examine the relationship between profitability, leverage and the size of the business (firmsize) on tax avoidance. The Sample used is 41 companies listed on the stock exchange in the period 2018-2019, sample determination using random sampling. The analysis tool used is linear regression multiple by using SPSS. Regression test results show that simultaneously profitability, leverage and business size (firmsize) influence significantly to tax avoidance, the test results also showed that these three variables have an effect of 35% on tax avoidance, meanwhile, partially profitability (NPM) has a negative influence and significant, leverage (DER) positive and insignificant effect, while firmsize has a negative and insignificant influence.